2012
DOI: 10.1074/mcp.m111.014969
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Structural Disorder in the Rewiring of Protein Interactions through Evolution

Abstract: Structurally disordered regions play a key role in proteinprotein interaction networks and the evolution of highly connected proteins, enabling the molecular mechanisms for multiple binding. However, the role of protein disorder in the evolution of interaction networks has only been investigated through the analysis of individual proteins, making it impossible to distinguish its specific impact in the (re)shaping of their interaction environments. Now, the availability of large interactomes for several model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 58 publications
2
50
0
Order By: Relevance
“…In all, it is rather clear from the examples of overrepresentation that their evolutionary inclusion provides functional advantage, which contributes to fixation of the shuffled exon because it modulates the function of the protein by either affecting activity of the protein or its interactions with partner proteins. This is fully in line with recent observations based on comparing the human, fly and yeast interactomes (36), in which disordered proteins/regions are preferentially involved in rewiring interaction patterns of proteins. In all, all these examples suggest that shuffling enabled by phase symmetry and structural compatibility with the recipient protein because of structural disorder are necessary but not sufficient conditions for the evolution fixation of the shuffled exon: functional compatibility of the novel element of motif/domain must also come into picture for lasting fixation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In all, it is rather clear from the examples of overrepresentation that their evolutionary inclusion provides functional advantage, which contributes to fixation of the shuffled exon because it modulates the function of the protein by either affecting activity of the protein or its interactions with partner proteins. This is fully in line with recent observations based on comparing the human, fly and yeast interactomes (36), in which disordered proteins/regions are preferentially involved in rewiring interaction patterns of proteins. In all, all these examples suggest that shuffling enabled by phase symmetry and structural compatibility with the recipient protein because of structural disorder are necessary but not sufficient conditions for the evolution fixation of the shuffled exon: functional compatibility of the novel element of motif/domain must also come into picture for lasting fixation.…”
Section: Discussionsupporting
confidence: 91%
“…Most of these motifs contribute novel protein–protein interaction sites (partner of SH3 domain and nuclear localization receptor) or post-translational modification site (sumoylation site), i.e. they extend the functionality of the recipient protein in a simple but straightforward way, in accord with recent results showing that disordered regions are often involved in rewiring protein–protein interaction networks (36). That is, their enrichment is a strong indication that their presence provided an adaptive advantage to the gene after shuffling, in accord with our conjecture that not only structural but also functional compatibility with the recipient protein drive the fixation of a shuffled exon.…”
Section: Resultssupporting
confidence: 73%
“…This supports the hypothesis that phenotypic divergence can result as the conformational flexibility changes, here rewiring protein–protein interaction networks. Further support is provided by a recent study that found interactomes to be depleted in conserved interactions mediated by disordered proteins as compared with ordered proteins networks (Mosca et al 2012). …”
Section: Discussionmentioning
confidence: 85%
“…To confirm our finding of the low mutability of the C-tail region, we also analyzed all human PTEN mutations deposited in the Human Gene Mutation Database (HGMD, http://www.hgmd.cf.ac.uk/ac/index.php)25 (Figure 2a), cBioPortal for Cancer Genomics2627 (Supplementary Figure S1) and the Roche Cancer Genome Database28 (Supplementary Figure S1) which was consistent with the COSMIC database mutational data. It is likely that evolutionary pressure maintains a survival advantage and ipso facto abrogates progeny with mutations in highly functional protein sequences293031. Thus, the functionally versatile PTEN C-tail IDR cannot afford mutations, hence showing least number of mutations.…”
Section: Resultsmentioning
confidence: 99%